Ceramic material as well as preparation method and application thereof

By preparing a porous lattice structure in titanium alloy, embedded ceramics and filled with aluminum alloys, the problem of ceramic fragility is solved, and the effective protection area and impact resistance of ceramic materials are significantly improved.

CN119710414APending Publication Date: 2025-03-28ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411919563.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Ceramic materials are prone to fragility when subjected to large impact forces, causing the armor to lose its protective effect. The effective protection area of ​​the ceramic is only about 50% of the surface, and the peripheral part does not have effective protection capabilities.

Method used

By preparing a porous dot matrix structure in titanium alloy, embedded ceramics and filled with aluminum alloys, forming interspersed arrangements of hard and soft materials, thereby improving the wrapping effect of the ceramics.

Benefits of technology

It realizes the tight constraints and effective wrapping of ceramics, significantly increases the effective protection area of ​​ceramic materials, and improves impact resistance and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710414A_ABST
    Figure CN119710414A_ABST
Patent Text Reader

Abstract

The invention provides a ceramic material as well as a preparation method and application thereof, and belongs to the technical field of ceramic materials. The ceramic material provided by the invention comprises a titanium alloy with a porous lattice structure, ceramic and an aluminum alloy, gaps are formed in the porous lattice structure; the ceramic is embedded in the gap; the porous lattice structure is filled with the aluminum alloy. The ceramic is embedded into the gaps of the titanium alloy, the porous lattice structure of the titanium alloy is filled with the aluminum alloy, the ceramic can be wrapped by the aluminum alloy and the titanium alloy, the interpenetration structure of the aluminum alloy and the titanium alloy is utilized, interpenetration arrangement of hard and soft materials is achieved, and therefore the wrapping effect on the ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a ceramic material and a preparation method and application thereof. Background Art

[0002] With the continuous progress and development of national defense technology, the performance requirements for protective armor materials are getting higher and higher. Ceramic materials are becoming increasingly important in applications that pursue lightweight while maintaining high protection capabilities due to their high hardness, high melting point, light weight and excellent crushing energy absorption characteristics. However, the high brittleness of ceramics makes them easy to break when subjected to large impact forces. This breakage may cause the armor to lose its protective effect after a major impact, and usually the effective protection area of ​​ceramics is only about 50% of the surface, and the ceramics in the outer part do not have effective protection capabilities.

[0003] To overcome these limitations, ceramic armor plates are usually combined with other materials such as metals or polymers to form composite armor, which combines the advantages of various materials to minimize the brittle defects of ceramics, thereby enhancing the protective effect and durability of the overall structure. Further research shows that when ceramics are tightly coated with other materials, their effective protection area will increase significantly, thereby improving the impact resistance and service life of ceramic protective plates. How to achieve ceramic coating has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0004] The object of the present invention is to provide a ceramic material and a preparation method and application thereof. The ceramic material provided by the present invention can wrap ceramic inside the material, and the material is dense as a whole and has no obvious defects.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a ceramic material, including a titanium alloy, ceramic and aluminum alloy with a porous lattice structure;

[0007] The porous lattice structure is provided with gaps;

[0008] The ceramic is embedded in the gap;

[0009] The aluminum alloy is filled in the porous lattice structure.

[0010] Preferably, the gap is cylindrical in shape.

[0011] Preferably, the diameter of the gap is 17-19 mm, and the height of the gap is 10-35 mm.

[0012] Preferably, the size of the structural unit in the porous lattice structure is 9×9×9 mm, 12×12×12 mm or 15×15×15 mm.

[0013] Preferably, the volume fraction of the structural unit is 10-30%.

[0014] The present invention also provides a method for preparing the ceramic material described in the above technical solution, comprising the following steps:

[0015] (1) Preparing titanium alloy by additive manufacturing method;

[0016] (2) embedding ceramic into the voids of the titanium alloy obtained in step (1) to obtain an intermediate;

[0017] (3) Casting the intermediate obtained in step (2) with aluminum alloy melt to obtain a ceramic material.

[0018] Preferably, in the step (1) of additive manufacturing, the scanning speed of the laser is 700 to 1300 mm / s, the power of the laser is 180 to 270 W, the scanning interval is 0.07 to 0.09 mm, and the scanning delay is 10 to 15 μs.

[0019] Preferably, the temperature of the aluminum alloy melt in step (3) is 680-720°C.

[0020] Preferably, the casting in step (3) is carried out in a low-pressure casting machine.

[0021] The present invention also provides the use of the ceramic material described in the above technical solution or the ceramic material prepared by the preparation method described in the above technical solution in a protective armor plate.

[0022] The present invention provides a ceramic material, including a titanium alloy, a ceramic and an aluminum alloy in a porous lattice structure; the porous lattice structure is provided with voids; the ceramic is embedded in the voids; and the aluminum alloy is filled in the porous lattice structure. The present invention embeds the ceramic in the voids of the titanium alloy, and the aluminum alloy fills the porous lattice structure of the titanium alloy so that the aluminum alloy and the titanium alloy can wrap the ceramic. The interpenetrating structure of the aluminum alloy and the titanium alloy is utilized to realize the interpenetrating arrangement of hard and soft materials, thereby improving the wrapping effect of the ceramic. Experimental results show that the ceramic is tightly constrained in the ceramic material, and the overall material is dense and defect-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the relationship curve between the constant C and the volume fraction of the structural unit;

[0024] Figure 2 This is a schematic diagram of the structure of a structural unit with a volume fraction of 10% in the titanium alloy of Example 1;

[0025] Figure 3 It is a schematic structural diagram of a top view of the titanium alloy in Example 1;

[0026] Figure 4 Schematic diagram of the structure of the titanium alloy in Example 1;

[0027] Figure 5 Schematic diagram of the structure of the titanium alloy in Example 1;

[0028] Figure 6 This is a schematic diagram of the structure of the top view of the intermediate in Example 1;

[0029] Figure 7 is a schematic diagram of the structure of the intermediate in Example 1;

[0030] Figure 8 is a schematic diagram of the structure of the intermediate in Example 1;

[0031] Fig. 9 Schematic diagram of the structure of the low pressure casting machine used in Example 1;

[0032] Fig.10 This is an industrial CT image of the ceramic material prepared in Example 1;

[0033] Fig.11 This is a schematic diagram of the structure of a structural unit with a volume fraction of 20% in the titanium alloy of Example 2;

[0034] Fig.12 This is the industrial CT image of the ceramic material prepared in Example 2. DETAILED DESCRIPTION

[0035] The present invention provides a ceramic material, including a titanium alloy, ceramic and aluminum alloy with a porous lattice structure;

[0036] The porous lattice structure is provided with gaps;

[0037] The ceramic is embedded in the gap;

[0038] The aluminum alloy is filled in the porous lattice structure.

[0039] In the present invention, the ceramic material includes a titanium alloy with a porous lattice structure; the porous lattice structure is provided with voids. In the present invention, the voids are used to fill ceramics, and the pores of the titanium alloy after the ceramics are filled, that is, the porous lattice structure is used to fill aluminum alloy, so that the aluminum alloy and the titanium alloy wrap the ceramics.

[0040] In the present invention, the shape of the void is preferably cylindrical; the diameter of the void is preferably 17 to 19 mm, more preferably 18 mm; the height of the void is preferably 10 to 35 mm. As an embodiment, the height of the void may be 20 mm or 30 mm.

[0041] The present invention has no special limitation on the height of the titanium alloy, as long as it is less than or equal to the height of the gap.

[0042] In the present invention, the titanium alloy preferably contains a plurality of voids; the plurality of voids are preferably arranged in parallel rows in the horizontal direction; the distance between the centers of two adjacent voids is preferably 19 to 21 mm, more preferably 20 mm.

[0043] In the present invention, the size of the structural unit in the porous lattice structure is preferably 9×9×9 mm, 12×12×12 mm or 15×15×15 mm; the volume fraction of the structural unit is preferably 10-30%. The present invention can adjust the porosity of the porous lattice structure by limiting the size of the structural unit within the above range.

[0044] As an implementation manner, the volume fraction of the structural unit may be 10%, 20% or 30%.

[0045] In the present invention, the mathematical formula of the structural unit is shown in Formula I:

[0046]

[0047] In Formula I, x, y, and z are the spatial coordinates of each surface point, and C is a constant. The present invention can obtain a porous lattice structure through Formula I.

[0048] The present invention uses C to adjust the volume fraction of the structural unit. The present invention has no special limitation on the operation of using C to adjust the volume fraction of the structural unit, and the operation can be performed according to common sense.

[0049] As an embodiment, the relationship between C and the volume fraction of the structural unit is as follows: Figure 1 shown.

[0050] from Figure 1 It can be seen that the constant C corresponds to the volume fraction of the structural unit.

[0051] In the present invention, the titanium alloy is preferably TC4, Ti-6Al-4V or Ti-6Al-7Nb.

[0052] In the present invention, the ceramic material further comprises ceramics; the ceramics are embedded in the gaps. In the present invention, the ceramics are hard materials used to improve the strength of the ceramic material.

[0053] In the present invention, the shape of the ceramic is preferably a cylinder. The present invention has no particular limitation on the size of the cylinder, as long as the gaps in the titanium alloy are completely filled.

[0054] In the present invention, the material of the ceramic is preferably SiC.

[0055] In the present invention, the ceramic material further comprises an aluminum alloy; the aluminum alloy is filled in the porous lattice structure. In the present invention, the aluminum alloy is a soft material used to improve the toughness of the ceramic material.

[0056] The present invention has no particular limitation on the shape of the aluminum alloy, as long as the gaps in the ceramic material are completely filled.

[0057] In the present invention, the aluminum alloy preferably includes the following chemical components in mass percentage: Si 6.0-8.0%, Cu 1.3-2.0%, Mg 0.2-0.4%, Mn 0.15-0.25%, Ti 0.05-0.15%, B 0.02-0.05%, Cr 0.05-0.1% and the balance Al.

[0058] As an implementation mode, the grade of the aluminum alloy may be A356.

[0059] The present invention embeds ceramics into the gaps of titanium alloy, and aluminum alloy fills the porous lattice structure of titanium alloy, so that the aluminum alloy and titanium alloy can wrap the ceramics, and utilizes the interpenetrating structure of the aluminum alloy and titanium alloy to achieve the interpenetrating arrangement of hard and soft materials, thereby improving the wrapping effect on the ceramics.

[0060] The present invention also provides a method for preparing the ceramic material described in the above technical solution, comprising the following steps:

[0061] (1) Preparing titanium alloy by additive manufacturing method;

[0062] (2) embedding ceramic into the voids of the titanium alloy obtained in step (1) to obtain an intermediate;

[0063] (3) Casting the intermediate obtained in step (2) with aluminum alloy melt to obtain a ceramic material.

[0064] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0065] The present invention adopts an additive manufacturing method to prepare titanium alloy.

[0066] In the present invention, the additive manufacturing method preferably comprises the following steps:

[0067] 1) Using computer software to construct a three-dimensional model of the titanium alloy and obtain the dimensional data of the titanium alloy;

[0068] 2) Performing additive manufacturing according to the dimensional data of the titanium alloy obtained in step 1) to obtain a titanium alloy.

[0069] The present invention preferably uses computer software to construct a three-dimensional model of the titanium alloy to obtain dimensional data of the titanium alloy.

[0070] The present invention has no special limitation on the operation of using computer software to construct a three-dimensional model of the titanium alloy and obtain the dimensional data of the titanium alloy, and the operation well known to those skilled in the art can be used.

[0071] The dimensional data of the titanium alloy is obtained. The present invention preferably performs additive manufacturing based on the dimensional data of the titanium alloy to obtain the titanium alloy.

[0072] In the present invention, the additive manufacturing is preferably carried out in a laser selective melting (SLM) device. The present invention has no special limitation on the model of the laser selective melting device, and any device well known to those skilled in the art can be used.

[0073] In the present invention, the substrate is preferably installed in the molding chamber of the laser selective melting device before the additive manufacturing. The present invention has no special limitation on the operation of installing the substrate in the molding chamber of the laser selective melting device, and the operation well known to those skilled in the art can be adopted. The installation of the substrate in the molding chamber of the laser selective melting device in the present invention can ensure the stability of the additive manufacturing process.

[0074] In the present invention, the process parameters of the laser selective melting equipment preferably include: the temperature of the substrate is 110-130°C, the feed base is 1.0-1.3, the feed multiple is 1.1-1.4, the flow rate of the fan is 3.0-4.0 m / s, the oxygen content is ≤0.1wt%, and the cabin pressure and the filter pressure difference are independently 40-50 mbar.

[0075] As an embodiment, the process parameters of the laser selective melting equipment can be: the temperature of the substrate is 115-125°C, the feed base is 1.1-1.2, the feed multiple is 1.2-1.3, the flow rate of the fan is 3.2-3.6 m / s, the oxygen content is ≤0.1wt%, and the cabin pressure and the filter pressure difference are independently 42-46 mbar.

[0076] In the present invention, the scanning speed of the laser in the additive manufacturing is preferably 700-1300 mm / s; the power of the laser is preferably 180-270 W; the scanning spacing of the laser is preferably 0.07-0.09 mm; and the scanning delay of the laser is preferably 10-15 μs. The present invention limits the process parameters of additive manufacturing within the above range to ensure the melting process and structural accuracy.

[0077] As an implementation mode, the scanning speed of the laser in the additive manufacturing can be 800-1200 mm / s, or 900-1000 mm / s; the power of the laser can be 190-250 W, or 230-240 W; the scanning spacing of the laser can be 0.075-0.08 mm; and the scanning delay of the laser can be 13-14 μs.

[0078] In the present invention, the additive manufacturing is preferably carried out in a protective atmosphere; the protective atmosphere is preferably argon. In the present invention, the additive manufacturing is carried out in a protective atmosphere to prevent oxidation.

[0079] After the additive manufacturing is completed, the present invention preferably performs post-processing on the product obtained by the additive manufacturing to obtain a titanium alloy.

[0080] In the present invention, the post-treatment is preferably alkaline washing, acid washing, alcohol washing, plating and drying performed in sequence.

[0081] In the present invention, the detergent used in the alkali washing is preferably a NaOH solution; the mass concentration of the NaOH solution is preferably 5-10%; the time of the alkali washing is preferably 10-20 minutes. The present invention limits the process parameters of the alkali washing to the above range to remove grease pollution on the surface of the titanium alloy.

[0082] As an implementation mode, the mass concentration of the NaOH solution may be 6-10%; and the alkali washing time may be 12-15 minutes.

[0083] In the present invention, the detergent used for pickling is preferably hydrochloric acid; the mass concentration of the hydrochloric acid is preferably 5-10%; the pickling time is preferably 10-20 minutes. The present invention limits the pickling process parameters within the above range to remove the oxide layer on the surface of the titanium alloy.

[0084] As an implementation mode, the mass concentration of the hydrochloric acid may be 6-10%; and the pickling time may be 12-15 minutes.

[0085] The present invention has no special limitation on the operation of the alcohol cleaning, and the operation familiar to the technicians of the present invention can be used to clean the titanium alloy. The alcohol cleaning of the present invention can ensure that the titanium alloy reaches the cleanliness standard required for low-pressure casting.

[0086] In the present invention, the plating solution used for the coating is preferably a mixed solution of K2ZrF6 and NaF; the mass concentration of K2ZrF6 in the mixed solution is preferably 8.3%; the mass concentration of NaF in the mixed solution is preferably 0.08%; the coating time is preferably 10 to 30 minutes; the coating temperature is preferably 60 to 90° C. The coating used in the present invention can prevent oxidation of titanium alloy.

[0087] As an implementation manner, the coating time may be 15 to 25 minutes; the coating temperature may be 70 to 90°C.

[0088] In the present invention, the drying temperature is preferably 150-250° C. and the drying time is preferably 10-15 minutes. The present invention adopts drying to ensure a more uniform coating.

[0089] After obtaining the titanium alloy, the present invention embeds ceramics into the gaps of the titanium alloy to obtain an intermediate.

[0090] In the present invention, the ceramic is preferably surface treated before use. The surface treatment of the ceramic in the present invention can improve the bonding effect between the ceramic and the metal.

[0091] In the present invention, the surface treatment preferably includes polishing, etching, modifying and drying performed in sequence.

[0092] The present invention has no special limitation on the grinding operation, and the operation well known to those skilled in the art can be adopted. The present invention can remove pollutants on the surface by grinding the ceramic surface.

[0093] In the present invention, the etching is preferably carried out in a hydrofluoric acid solution; the mass concentration of the hydrofluoric acid solution is preferably 5 to 10%; and the etching time is preferably 5 to 20 minutes. The present invention has no special limitation on the etching temperature, and it can be carried out at room temperature. The present invention uses etching to remove the natural oxide layer and other impurities on the ceramic surface to expose a fresh surface and enhance its chemical bonding with the metal.

[0094] As an implementation manner, the mass concentration of the hydrofluoric acid solution may be 6-8%; and the etching time may be 10-15 minutes.

[0095] In the present invention, the modification is preferably carried out in a silane coupling agent solution; the mass concentration of the silane coupling agent solution is preferably 0.5-2%; the silane coupling agent is preferably 3-aminopropyltriethoxysilane; the modification time is preferably 5-30 minutes. The present invention has no special limitation on the temperature of the modification, and it can be carried out at room temperature. The modification of the present invention can improve the bonding strength between ceramics and metals.

[0096] As an implementation mode, the mass concentration of the silane coupling agent solution may be 1.0-1.5%; the modification time may be 8-25 minutes, or 15-20 minutes.

[0097] In the present invention, the drying temperature is preferably 200°C; the drying time is preferably 10 to 15 minutes. In the drying process of the present invention, the silane molecules will self-assemble to form a monolayer, which not only promotes chemical bonding with the metal melt, but also acts as a stress buffer layer to reduce the internal stress caused by the difference in thermal expansion coefficient.

[0098] The present invention has no special limitation on the operation of embedding the ceramic into the gap of the titanium alloy, and the operation can be performed according to common sense.

[0099] After obtaining the intermediate, the present invention casts the intermediate with aluminum alloy melt to obtain a ceramic material.

[0100] In the present invention, the casting is preferably carried out in a low-pressure casting machine. The present invention has no special limitation on the type of the low-pressure casting machine, and any equipment well known to those skilled in the art can be used.

[0101] In the present invention, the upper cavity of the low-pressure casting machine is preferably preheated before casting; the preheating temperature is preferably 250-400°C; and the preheating time is preferably ≥15 minutes. The present invention preheats the upper cavity of the low-pressure casting machine to ensure uniform temperature distribution in the upper cavity, eliminate any potential temperature differences, and make adequate preheating preparations for the casting process.

[0102] In the present invention, the temperature of the aluminum alloy melt is preferably 680-720° C. As an embodiment, the temperature of the aluminum alloy melt may be 690-700° C.

[0103] In the present invention, the aluminum alloy melt is preferably melted in the lower cavity of a low-pressure casting machine; the melting process parameters preferably include: a melting temperature of 680-720°C, a current of 1000-1500A for the electromagnetic pump electrode, a current of 40-60A for the electromagnetic coil, and a melting time of ≥1h. The present invention limits the melting process parameters within the above range to ensure that the aluminum alloy is completely melted and ready for the subsequent casting process.

[0104] In the present invention, the vacuum degree of the upper chamber during smelting is preferably 2×10 -1 Pa. The present invention controls the vacuum degree of the upper chamber to 2×10 -1 In a high vacuum environment like Pa, the molten aluminum alloy can fill the pores of the titanium alloy more effectively, greatly reducing the phenomenon of leaking castings; in addition, the high vacuum state of the upper cavity also helps to form an air pressure difference with the lower cavity, promoting the molten aluminum alloy in the lower cavity to rise smoothly to the upper cavity mold, which not only optimizes the filling effect of the molten aluminum alloy, but also reduces energy consumption by reducing the demand for pressurization of the lower cavity.

[0105] In the present invention, the pressure of the lower cavity during casting is preferably 0.3-0.6 MPa. The present invention limits the pressure of the lower cavity within the above range to form a significant pressure difference with the upper cavity, which causes the aluminum alloy melt in the lower cavity to be pressed into the upper cavity mold to form a solid-liquid composite with the intermediate.

[0106] As an implementation mode, the pressure of the lower cavity during the casting may be 0.4-0.5 MPa.

[0107] In the present invention, the lower chamber pressure is preferably maintained for 10 to 25 minutes. The present invention limits the lower chamber pressure maintenance time to the above range to ensure that the aluminum alloy melt can evenly fill the mold and form a uniform and stable interpenetrating structure with the composite material.

[0108] After the casting is completed, the present invention preferably performs grinding and cutting processes on the product obtained by casting in sequence to obtain a ceramic material.

[0109] The present invention has no particular limitation on the grinding operation, as long as the burrs and rough parts on the surface of the product obtained by casting can be removed.

[0110] The present invention has no special limitation on the cutting operation, and cutting operations well known to those skilled in the art may be used to achieve the desired target size.

[0111] The present invention first adopts additive manufacturing technology to prepare a pre-embedded ceramic titanium alloy rod frame with a porous lattice structure; then, the titanium alloy and ceramic are surface treated, and the treated ceramic is assembled with the rod frame and installed in a low-pressure casting mold; finally, by adjusting the preheating, smelting, upper chamber vacuuming, lower chamber pressurization and other steps of the low-pressure casting machine, a pressure difference is formed between the pressurization of the lower chamber and the upper chamber in a vacuum state, so that the aluminum alloy melt fully fills the casting mold from bottom to top to obtain an interpenetrating structure ceramic material. The present invention makes full use of the high hardness, high melting point and excellent crushing energy absorption characteristics of ceramics to provide impact protection, and at the same time combines lightweight titanium-aluminum interpenetrating structure materials, improves the fragility of ceramics through strong and tough synergistic effects, and uses the shrinkage stress solidified during the casting process to seal and coat the ceramics, significantly increasing the effective protection area of ​​the ceramic material.

[0112] The present invention uses additive manufacturing technology to prepare a porous lattice structure bracket, so that the ceramic can be accurately placed in a predetermined position. At the same time, the present invention ensures that the aluminum alloy melt can effectively fill and coat the ceramic protective material during the low-pressure casting process, realize the interpenetrating arrangement of hard and soft materials, and the combination of metallurgy and mechanics, thereby improving the strength and overall toughness of the composite armor plate and improving the hardness and brittleness of the ceramic. This method can prepare a packaged ceramic plate protective material with an interpenetrating structure in one step.

[0113] The coating materials of the present invention are lightweight titanium alloy and aluminum alloy. The significant differences in the physical and chemical properties of these two materials enable the formation of a strong bionic interpenetrating structure, which improves the mechanical properties of the protective plate as a whole. Compared with the traditional top-down casting method, the present invention adopts low-pressure casting technology to control the liquid metal to fill the mold from bottom to top through the air pressure difference. This method makes the liquid flow more stable, reduces turbulence, and thus reduces the generation of pores and inclusions. At the same time, the uniform cooling of the casting helps to reduce thermal cracking and stress concentration. In addition, low-pressure casting technology is more suitable for mass production of products with complex shapes, has a higher degree of automation, and effectively reduces labor intensity and operational difficulty.

[0114] The present invention also provides the use of the ceramic material described in the above technical solution or the ceramic material prepared by the preparation method described in the above technical solution in a protective armor plate.

[0115] The present invention has no special limitation on the operation of applying the ceramic material in the protective armor plate, and the operation well known to those skilled in the art can be adopted.

[0116] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0117] Example 1

[0118] The ceramic material is composed of titanium alloy, ceramic and aluminum alloy with porous lattice structure;

[0119] The porous lattice structure is provided with gaps;

[0120] The ceramic is embedded in the gap;

[0121] The aluminum alloy is filled in the porous lattice structure;

[0122] The shape of the gap is cylindrical; the diameter of the gap is 18 mm and the height is 20 mm;

[0123] The titanium alloy contains 9 voids; the 9 voids are arranged in parallel rows in the horizontal direction; the distance between the centers of two adjacent voids is 20 mm;

[0124] The gaps are arranged in three rows and three columns on the same horizontal plane;

[0125] The size of the structural unit in the porous lattice structure is 12×12×12 mm; the volume fraction of the structural unit is 10%;

[0126] The titanium alloy is TC4;

[0127] The ceramic is in the shape of a cylinder and is made of SiC;

[0128] The grade of the aluminum alloy is A356;

[0129] The mathematical formula of the structural unit in the porous lattice structure is shown in Formula I:

[0130]

[0131] In formula I, x, y, z are the spatial coordinates of each surface point, and C is a constant;

[0132] The preparation method of the ceramic material comprises the following steps:

[0133] (1) Use Matlab software to build a three-dimensional model of titanium alloy: After completing the 10% volume fraction design, export the model file into x_t format, then import the model into Magics 24.0 software, set the size of the structural unit to 12×12×12 mm, drag the model to the processing platform interface, and perform the slicing operation to generate a Cli file. After completing the preliminary slicing, open the EPHatch software, select the titanium alloy process package for re-slicing, confirm the filling parameters and save the settings to obtain the dimensional data of the titanium alloy;

[0134] (2) Install the titanium substrate in the molding chamber, then evenly fill the powder bin with titanium alloy powder. Next, set the key process parameters of the laser selective melting equipment: set the substrate temperature to 120°C, adjust the feed base to 1.1, set the feed multiple to 1.2, set the fan flow rate to 3.5m / s, control the oxygen content within 0.1wt%, and set the chamber pressure and filter pressure difference to 45mbar; set the laser scanning speed to 1000mm / s, adjust the laser power to 230W, set the scanning interval to 0.08mm, and the scanning delay to 12μs. Finally, Fill the molding chamber with argon gas, start the equipment for additive manufacturing, immerse it in a beaker containing a 5% mass concentration NaOH solution after the alkali washing, and perform alkaline washing for 20 minutes. After the alkaline washing is completed, transfer it to a beaker containing a 5% mass concentration hydrochloric acid solution for acid washing for 20 minutes. After acid washing, use alcohol to thoroughly clean the titanium alloy, immerse the cleaned titanium alloy in a plating agent solution containing 8.3wt% K2ZrF6 and 0.08wt% NaF at a temperature of 80°C for 20 minutes, and then take it out and place it in an oven at 200°C for drying for 15 minutes to obtain a titanium alloy;

[0135] (3) grinding the ceramic surface with sandpaper, then etching with a 5wt% hydrofluoric acid solution for 10 minutes, then soaking the ceramic in a 1wt% 3-aminopropyltriethoxysilane solution for 15 minutes, then taking it out and drying it in a drying oven at 200°C for 15 minutes, and then accurately placing the surface-treated ceramic in the cylindrical void of the titanium alloy obtained in step (2) to obtain an intermediate;

[0136] (4) placing the intermediate obtained in step (3) in the lower mold of the upper chamber of the low-pressure casting machine, installing the upper mold and performing the mold closing operation, then activating the preheating system of the upper chamber, and correctly inserting the heating rod into the preheating hole designed in the mold, setting the preheating temperature to 350°C and maintaining the temperature for 15 minutes; then opening the lower chamber, and filling the aluminum alloy into it, closing the chamber, starting the smelting heating system, setting the current output of the electromagnetic pump electrode to 1300A in the control system, while maintaining the current intensity in the electromagnetic coil to 50A, and the smelting temperature to 700°C, maintaining the temperature for 1 hour, and using a vacuum pump to evacuate the upper chamber of the low-pressure casting machine to 3.0×10 2 Pa, then start the diffusion pump to set the vacuum degree of the upper chamber to 2×10 -1 Pa; then start casting the aluminum alloy melt, inflate the lower cavity of the low-pressure casting machine, adjust the pressure to 0.4MPa for 15 minutes, so that the aluminum alloy melt in the lower cavity is pressed into the upper cavity mold, and forms a solid-liquid composite with the intermediate. After the casting is completed, use a grinding wheel to remove burrs and rough parts on the surface of the casting, and then use a CNC machine tool to perform precise cutting to obtain a ceramic material.

[0137] Example 1 The schematic diagram of the structure of the structural unit with a volume fraction of 10% in the titanium alloy is as follows Figure 2 shown.

[0138] from Figure 2 It can be seen that the titanium alloy has a porous lattice structure.

[0139] The schematic diagram of the top view of the titanium alloy in Example 1 is as follows Figure 3 As shown; the structural schematic diagram of the titanium alloy in Example 1 is as shown Figure 4 and 5 shown.

[0140] from Figures 3 to 5 It can be seen that the titanium alloy of the present invention is a porous lattice structure, in which cylindrical voids are arranged, and the cylindrical voids are arranged in the same horizontal plane, in three rows and three columns.

[0141] The schematic diagram of the top view of the intermediate in Example 1 is as follows Figure 6 As shown; the schematic diagram of the structure of the intermediate in Example 1 is as shown Figure 7 and8 shown.

[0142] from Figures 6 to 8 The structures of the intermediates of the present invention can be clearly understood.

[0143] The structural schematic diagram of the low pressure casting machine used in Example 1 is as follows Fig. 9 shown.

[0144] Industrial CT scanning technology was used to perform defect analysis on the interior of the ceramic material prepared in Example 1.

[0145] The industrial CT image of the ceramic material prepared in Example 1 is as follows Fig.10 shown.

[0146] from Fig.10 It can be seen that the black titanium alloy rod frame and the gray aluminum alloy have achieved a good interpenetrating structure, and there are no cracks and pores at the interface. Further observation shows that the light gray shadow in the center of the image is the projection of the cylindrical protective ceramic on the vertical plane. The ceramic with a diameter of 18mm and a height of 20mm is tightly constrained in it, and the overall material is dense and defect-free.

[0147] Example 2

[0148] The ceramic material is composed of titanium alloy, ceramic and aluminum alloy with porous lattice structure;

[0149] The porous lattice structure is provided with gaps;

[0150] The ceramic is embedded in the gap;

[0151] The aluminum alloy is filled in the porous lattice structure;

[0152] The shape of the gap is cylindrical; the diameter of the gap is 18 mm and the height is 30 mm;

[0153] The titanium alloy contains 9 voids; the 9 voids are arranged in parallel rows in the horizontal direction; the distance between the centers of two adjacent voids is 20 mm;

[0154] The gaps are arranged in three rows and three columns on the same horizontal plane;

[0155] The size of the structural unit in the porous lattice structure is 15×15×15 mm; the volume fraction of the structural unit is 20%;

[0156] The mathematical formula of the structural unit in the porous lattice structure is shown in Formula I:

[0157]

[0158] In formula I, x, y, z are the spatial coordinates of each surface point, and C is a constant;

[0159] The titanium alloy is Ti-6Al-7Nb;

[0160] The ceramic is in the shape of a cylinder and is made of SiC;

[0161] The grade of the aluminum alloy is A356;

[0162] The preparation method of the ceramic material comprises the following steps:

[0163] (1) Use UG software to construct a three-dimensional model of titanium alloy: After completing the 20% volume fraction design, export the model file into x_t format. Then, import the model into Magics 24.0 software, set the size of the structural unit to 15×15×15 mm, drag the model to the processing platform interface, and perform the slicing operation to generate a Cli file. After completing the initial slicing, open the EPHatch software, select the titanium alloy process package for re-slicing, confirm the filling parameters and save the settings to obtain the dimensional data of the titanium alloy.

[0164] (2) Install a titanium substrate in the molding chamber, then evenly fill the powder bin with titanium alloy powder, and then set the key process parameters of the laser selective melting equipment: set the substrate temperature to 120°C, adjust the feed base to 1.1, set the feed multiple to 1.2, set the fan flow rate to 3.5m / s, control the oxygen content within 0.1wt%, and set the chamber pressure and filter pressure difference to 45mbar; set the laser scanning speed to 1200mm / s, adjust the laser power to 240W, set the scanning interval to 0.08mm, and the scanning delay to 13μs. Finally, The molding chamber is filled with argon gas, and the equipment is started for additive manufacturing. After completion, it is immersed in a beaker containing a 10% mass concentration NaOH solution for 15 minutes of alkaline washing. After the alkaline washing is completed, it is transferred to a beaker containing a 10% mass concentration hydrochloric acid solution for 15 minutes of acid washing. After acid washing, the titanium alloy is thoroughly cleaned with alcohol, and the cleaned titanium alloy is immersed in a plating agent solution containing 8.3wt% K2ZrF6 and 0.08wt% NaF at a temperature of 90°C for 15 minutes. After that, it is taken out and placed in an oven at 200°C for drying for 10 minutes to obtain a titanium alloy;

[0165] (3) grinding the ceramic surface with sandpaper abrasive, then etching with 8wt% hydrofluoric acid solution for 15 minutes, then immersing the ceramic in 1wt% 3-aminopropyltriethoxysilane solution for 8 minutes, then taking it out and drying it in a drying oven at 200°C for 15 minutes, and then accurately placing the surface-treated ceramic in the cylindrical void of the titanium alloy obtained in step (2) to obtain an intermediate;

[0166] (4) placing the intermediate obtained in step (3) in the lower mold of the upper chamber of the low-pressure casting machine, installing the upper mold and performing the mold closing operation, then activating the preheating system of the upper chamber, and correctly inserting the heating rod into the preheating hole designed in the mold, setting the preheating temperature to 400°C and maintaining the temperature for 15 minutes; then opening the lower chamber, and filling the aluminum alloy into it, closing the chamber, starting the smelting heating system, setting the current output of the electromagnetic pump electrode to 1200A in the control system, while maintaining the current intensity in the electromagnetic coil to 40A, and the smelting temperature to 680°C, maintaining the temperature for 1 hour, and using a vacuum pump to evacuate the upper chamber of the low-pressure casting machine to 3.0×10 2 Pa, then start the diffusion pump to set the vacuum degree of the upper chamber to 2×10 -1 Pa; then start casting the aluminum alloy melt, inflate the lower cavity of the low-pressure casting machine, adjust the pressure to 0.5MPa for 15 minutes, so that the aluminum alloy melt in the lower cavity is pressed into the upper cavity mold, and forms a solid-liquid composite with the intermediate. After the casting is completed, use a grinding wheel to remove burrs and rough parts on the surface of the casting, and then use a CNC machine tool to perform precise cutting to obtain a ceramic material.

[0167] Example 2 The schematic diagram of the structure of the structural unit with a volume fraction of 20% in the titanium alloy is as follows Fig.11 shown.

[0168] from Fig.11 It can be seen that the titanium alloy has a porous lattice structure.

[0169] Industrial CT scanning technology was used to perform defect analysis on the interior of the ceramic material prepared in Example 2.

[0170] The industrial CT image of the ceramic material prepared in Example 2 is as follows Fig.12 shown.

[0171] from Fig.12 It can be seen that the black titanium alloy rod frame and the gray aluminum alloy have achieved a good interpenetrating structure, and there are no cracks and pores at the interface. Further observation shows that the light gray shadow in the center of the image is the projection of the cylindrical protective ceramic on the vertical plane. The ceramic with a diameter of 18mm and a height of 30mm is tightly constrained in it, and the overall material is dense and defect-free.

[0172] contrast Fig.10 and Fig.12 It can be seen that the black rod frame with a volume fraction of 10% in Example 1 occupies a smaller space, and under the effect of projection, the overall frame form is displayed in a more regular form; while the black titanium alloy rod frame with a volume fraction of 20% in Example 2 occupies a significantly larger space, the rod frame unit is thicker, similar to the connection between balls, and the frame projection is relatively disordered.

[0173] It can be seen from the above embodiments that the ceramic material provided by the present invention can well constrain and package ceramics, and the overall material is dense and has no obvious defects.

[0174] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A ceramic material comprising a titanium alloy, a ceramic and an aluminum alloy with a porous lattice structure; The porous lattice structure is provided with gaps; The ceramic is embedded in the gap; The aluminum alloy is filled in the porous lattice structure.

2. The ceramic material according to claim 1, characterized in that The shape of the void is cylindrical.

3. The ceramic material according to claim 1 or 2, characterized in that: The diameter of the gap is 17-19 mm, and the height of the gap is 10-35 mm.

4. The ceramic material according to claim 1, characterized in that The size of the structural unit in the porous lattice structure is 9×9×9 mm, 12×12×12 mm or 15×15×15 mm.

5. The ceramic material according to claim 4, characterized in that The volume fraction of the structural unit is 10-30%.

6. The method for preparing the ceramic material according to any one of claims 1 to 5, comprising the following steps: (1) Preparing titanium alloy by additive manufacturing method; (2) embedding ceramic into the voids of the titanium alloy obtained in step (1) to obtain an intermediate; (3) Casting the intermediate obtained in step (2) with aluminum alloy melt to obtain a ceramic material.

7. The preparation method according to claim 6, characterized in that: In the step (1) of additive manufacturing, the scanning speed of the laser is 700-1300 mm / s, the power of the laser is 180-270 W, the scanning interval is 0.07-0.09 mm, and the scanning delay is 10-15 μs.

8. The preparation method according to claim 6, characterized in that: The temperature of the aluminum alloy melt in step (3) is 680-720°C.

9. The preparation method according to claim 6, characterized in that: The casting in step (3) is carried out in a low pressure casting machine.

10. Use of the ceramic material according to any one of claims 1 to 5 or the ceramic material prepared by the preparation method according to any one of claims 6 to 9 in protective armor plates.